Text mining approach to predict hospital admissions using early medical records from the emergency department. (April 2017) - Lucini, Filipe R.; Fogliatto, Flavio S.; da Silveira, Giovani J.C.; Neyeloff, Jeruza L.; Anzanello, Michel J.; Kuchenbecker, Ricardo S.; Schaan, Beatriz D.
Highlights: This is the first study using text mining to estimate emergency bed demands. Our approach is able to estimate future bed demand using only textual information. We provide a powerful tool to use the text information in medical reports. Nu-SVC average F1 -score was 77.70% thus representing a good estimator. Abstract: Objective: Emergency department (ED) overcrowding is a serious issue for hospitals. Early information on short-term inward bed demand from patients receiving care at the ED may reduce the overcrowding problem, and optimize the use of hospital resources. In this study, we use text mining methods to process data from early ED patient records using the SOAP framework, and predict future hospitalizations and discharges. Design: We try different approaches for pre-processing of text records and to predict hospitalization. Sets-of-words are obtained via binary representation, term frequency, and term frequency-inverse document frequency. Unigrams, bigrams and trigrams are tested for feature formation. Feature selection is based on χ 2 and F-score metrics. In the prediction module, eight text mining methods are tested: Decision Tree, Random Forest, Extremely Randomized Tree, AdaBoost, Logistic Regression, Multinomial Naïve Bayes, Support Vector Machine (Kernel linear) and Nu-Support Vector Machine (Kernel linear). Measurements: Prediction performance is evaluated by F1-scores. Precision and Recall values are also informed for all text mining methods tested. Results: Nu-Support Vector Machine was the text mining method with the best overall performance. Its average F1-score in predicting hospitalization was 77.70%, with a standard deviation (SD) of 0.66%. Conclusions: The method could be used to manage daily routines in EDs such as capacity planning and resource allocation. Text mining could provide valuable information and facilitate decision-making by inward bed management teams.